2021
DOI: 10.3390/nu13092999
|View full text |Cite
|
Sign up to set email alerts
|

Tap Water Consumption and Perceptions in United States Latinx Adults

Abstract: Insufficient water intake is associated with adverse health outcomes, including chronic disease prevalence and mortality. Adherence to Institute of Medicine total water intake (TWI) recommendations has been low in recent decades, and TWI has been consistently lower in Latinx adults compared with non-Hispanic (NH) white adults. While overall plain water intake is similar between Latinx and NH white adults, Latinx adults consistently consume significantly more bottled water and less tap water. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Data from the United States of America (US) indicate that sugar-sweetened beverage consumption is decreasing while water intake is increasing (Vieux et al, 2020 ), despite decreases in overall total FI in younger adults (Colburn and Kavouras, 2021 ); this may indicate a shift in FI behaviors related to fluid type or composition rather than volume consumption. This is in comparison with data from Australia (AUS) that highlighted a matched proportion of fluid volume (37%) from plain water and from other beverages, with the remainder being consumed via moisture from foods (Sui et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the United States of America (US) indicate that sugar-sweetened beverage consumption is decreasing while water intake is increasing (Vieux et al, 2020 ), despite decreases in overall total FI in younger adults (Colburn and Kavouras, 2021 ); this may indicate a shift in FI behaviors related to fluid type or composition rather than volume consumption. This is in comparison with data from Australia (AUS) that highlighted a matched proportion of fluid volume (37%) from plain water and from other beverages, with the remainder being consumed via moisture from foods (Sui et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified multiple factors such as flavor, safety risk perception, prior experience, and trust in water utilities as contributors to consumer’s perception of water quality, which ultimately influences their consumption and choice of water [ 47 , 48 , 82 , 83 , 84 ]. In this study, lower drinking water intake in older adults aged 60–84 years coincided with lower sensitivity to metallic flavor; however, reduced taste sensitivity may not necessarily be associated with reduced consumption levels as indicated by a recent study that reported tap water consumers showed similar taste sensitivity to chlorine but differed in their acceptability of chlorine flavor [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…These descriptions agree with our previous formative work in this community, where tap water in the USA was described as being ‘recycled from the toilet’, in contrast to drinking water in their home countries in Central America because they knew the water source ( 24 ) . Hispanic households in the USA are among the groups with the lowest use of water filtration systems; this makes sense in view of the theory that people who are seriously concerned about the safety and contamination of tap water consume more bottled water, whereas those who have water filtration systems are only primarily concerned with the taste and organoleptic qualities of drinking water ( 37 , 38 ) . This could partially explain why at baseline, participants in the current study only drank bottled water, and why there was persistent mistrust in drinking tap water even after participants had received a water filter.…”
Section: Discussionmentioning
confidence: 99%
“…This could partially explain why at baseline, participants in the current study only drank bottled water, and why there was persistent mistrust in drinking tap water even after participants had received a water filter. Mistrust in tap water has been attributed to a myriad of interrelated factors, including early life experiences with water insecurity, built and contextual environment and geography, among others ( 38 , 39 ) . Mistrust in tap water and the water systems can also reflect larger and historical dynamics of social inequities and mistrust of government institutions ( 40 ) .…”
Section: Discussionmentioning
confidence: 99%